ANTI-CYTOKINE THERAPY FOR CHILDREN WITH INFLAMMATORY BOWEL DISEASES - A.S. Potapov; E.G. Tsimbalova; N.L. Pakhomovskaya (Педиатрическая фармакология, 2009)
The article describes the findings of a pilot research devoted to the estimation of the efficiency of a therapy with TNF α inhibitors for children with inflammatory bowel diseases. Methods: we carried out the retrospective analysis for a therapy with Infliximab in 15 children with a nonspecific ulcerative colitis and Сrohn's disease. Results: 66% of the children with inflammatory bowel diseases react to the first injection of Infliximab, whereas 13% of the children demonstrate a clinical remission of their diseases. After the third injection, a positive response to the used therapy is shown by 60% of the children with inflammatory bowel diseases, and 33% of the children are diagnosed with a clinical remission. Conclusion: The use of Infliximab allowed the children with a refractory course of nonspecific ulcerative colitis and Сrohn's disease to make their inflammation significantly less active and improve the quality of their life.Key words: nonspecific ulcerative colitis, Сrohn's disease, treatment, TNF α inhibitors, children